THE CHEMISTRY OF THE LIVER IN ACUTE YELLOW ATROPHY - Wells, H. Gideon (The Rockefeller University Press, 1907)
From the liver of a young man who died of typical, " idiopathic" acute yellow atrophy of the liver, after an illness of six weeks, there were isolated and identified the following amino acids: Histidin, lysin, tyrosin, leucin, glycocoll, alanin, prolin, glutaminic acid, aspartic acid. These were found free in extracts of the liver, and presumably represent products of the autolysis of liver cells, although the amount of soluble non-protein nitrogen present in the extracts was so large as to suggest that there must be some other source for these substances. Small quantities of free proteoses and peptones, and of xanthin and hypoxanthin, were also found in the extracts. In the insoluble proteins of the liver the proportion of diamino acids was decreased slightly as compared with normal livers. The proportion of protein phosphorus was increased, probably because of active regenerative proliferation, while the sulphur was normal in amount. Iron was increased because of the large quantity of blood in the liver and the hematogenous pigmentation of the liver cells. Gelatigenous material was increased both absolutely and relatively, because of the loss of parenchyma and the proliferation of the stroma. The proportion of water to solids was much increased, there having been a loss of over two-thirds of the entire parenchymatous elements of the liver. The amount of fat, lecithin and cholesterin was not far from that normal for the liver.